Strategi Dai untuk Meningkatkan Minat Belajar dan Pemahaman Pendidikan Agama Islam di Majelis Taklim Baiturrahman Kota Lhokseumawe - Husaini, Muhammad; Musdar, Musdar; Syahrizal, Syahrizal; Husaini, Husaini (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This research aims to explore the strategies employed by the preacher (Dai) to enhance interest and understanding in Islamic Religious Education within small groups, particularly at the Majelis Taklim Muslimat Baiturrahman in Lhokseumawe. The study encompasses efforts to comprehend the dynamics of small groups and seeks holistic and diverse approaches to religious education. Employing a qualitative case study approach, the research utilizes participatory observation techniques, semi-structured interviews, and document analysis. Data is collected from members of the study group and religious teachers to gain a profound understanding of the strategies employed. Data analysis employs an interactive qualitative approach to detail comprehensive findings. The research findings indicate that religious teachers actively employ three main strategies: 1) Interactive discussions create a collaborative environment that enhances active participation and enriches the learning experience. 2) Inspirational lectures elicit emotional stimulation by linking the subject matter to everyday life. 3) Question-and-answer approaches stimulate critical thinking and responsiveness to individual learning needs. The impacts of these strategies include increased interest in learning, the development of a deeper understanding, and the formation of a sense of unity among participants. Based on the research findings, it is recommended that religious teachers undergo training in implementing innovative strategies that can better adapt to the dynamics of small groups. Additionally, the results offer guidance for the development of instructional strategies focusing on participant engagement and the relevance of religious concepts in everyday life.